40.4k views
5 votes
Hurryyyy uppppp i need it rnn plzzz! Solve for f: 6f + 9g = 3g + f

f = f equals StartFraction negative 8 g Over 3 EndFraction.
f = f equals StartFraction negative 6 g Over 5 EndFraction.
f = f equals StartFraction negative 5 g Over 6 EndFraction.
f = f equals StartFraction 12 g Over 7 EndFraction.

User Tugrul
by
6.1k points

2 Answers

4 votes

Answer:

f=-6/5

Explanation:

got it from photomath

User Reachgoals
by
5.6k points
4 votes

Answer:


f=(-6g)/(5)

Explanation:

The given equation is:
6f + 9g = 3g + f.

To solve for f, first we should move all f's to the left side, and the other terms to the right side. The first goal is to reduce like term:


6f-f=3g-9g\\5f=-6g

Now, we isolate f, and then we'll have the final expression.


f=(-6g)/(5)

Therefore, the answer is
f=(-6g)/(5)

User Leoa
by
5.8k points